2017
DOI: 10.18332/tpc/67273
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory response to exercise of nonsmokers occupationally exposed to second hand smoke (SHS)

Abstract: INTRODUCTION Occupational exposure to Second Hand Smoke (SHS) continues to be an issue, even in countries with strong tobacco control legislation. The current study assessed the effect of chronic occupational exposure to SHS on cardiorespiratory exercise response among healthy adult non-smokers. METHODS 60 healthy non-smokers; 38 men, 22 women, aged 18-58 years with body mass index (BMI)<30 were separated into exposed to occupational SHS (exposed, n=30) and those non-exposed (controls, n=30) to occupational S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(46 reference statements)
2
4
0
Order By: Relevance
“…Irrespective of the compliance of the waterpipe HWL with the FCTC recommendations on the tobacco pack, the lack of exposure to the tobacco pack in café settings means that a considerable proportion of the targeted population is not reached. In line with other studies 9 , 20 , 21 , we found that placing the HWL on the mouthpiece would make it most noticeable for both males and females. While a prior study suggested that this location would be the most effective for non-users 16 , our study suggests that placing a health warning on the mouthpiece is also effective for current waterpipe smokers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Irrespective of the compliance of the waterpipe HWL with the FCTC recommendations on the tobacco pack, the lack of exposure to the tobacco pack in café settings means that a considerable proportion of the targeted population is not reached. In line with other studies 9 , 20 , 21 , we found that placing the HWL on the mouthpiece would make it most noticeable for both males and females. While a prior study suggested that this location would be the most effective for non-users 16 , our study suggests that placing a health warning on the mouthpiece is also effective for current waterpipe smokers.…”
Section: Discussionsupporting
confidence: 92%
“…These variations emphasize the importance of targeted interventions and policies in café settings and those targeting café-only smokers. Our study also confirms previous policy recommendations related to placing the targeted HWL on the waterpipe device, especially the mouthpiece 14 , 20 , 21 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, an analysis of seven Air Force technical trainee recruitment cohorts between April 2013 and December 2014 demonstrated a 6% prevalence of ENDS use among trainees 10 . A small Navy study in Jacksonville, Florida, concluded that nearly 30% of Naval SMs had tried ENDS, and 9.3% were current users 12 . That study found similar associations between ENDS use and income and education as found in this study 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A small Navy study in Jacksonville, Florida, concluded that nearly 30% of Naval SMs had tried ENDS, and 9.3% were current users 12 . That study found similar associations between ENDS use and income and education as found in this study 12 . An analysis of US Army infantry soldiers in Hawaii found 20% prevalence of ENDS use 11 .…”
Section: Discussionmentioning
confidence: 99%